2022
DOI: 10.3389/fnmol.2022.919718
|View full text |Cite
|
Sign up to set email alerts
|

Nedd4-2 Haploinsufficiency in Mice Impairs the Ubiquitination of Rer1 and Increases the Susceptibility to Endoplasmic Reticulum Stress and Seizures

Abstract: Neural precursor cell expressed developmentally downregulated gene 4-like (NEDD4-2) is an epilepsy-associated gene encoding an E3 ligase that ubiquitinates neuroactive substrates. An involvement of NEDD4-2 in endoplasmic reticulum (ER) stress has been recently found with mechanisms needing further investigations. Herein, Nedd4-2+/− mice were found intolerant to thapsigargin (Tg) to develop ER stress in the brain. Pretreatment of Tg aggravated the pentylenetetrazole (PTZ)-induced seizures. Retention in endoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Curiously, however, in the absence of a functional Pro-Gly-Try 1945 motif, it is observed that p38 phosphorylation of Nav 1.6 enhances peak current density [ 122 ], indicating that p38 phosphorylation of Nav1.6 may have opposing effects on Nav1.6-mediated neuronal excitability dependent on the function of Nedd4-2. Haploinsufficiency of Nedd4-2 is linked to increased seizure susceptibility [ 151 ], which is a hallmark symptom of prodromal AD [ 30 , 66 , 67 ]. Thus, it is possible that dysfunctional Nedd4-2 reduces Nav1.6 internalization and allows functional upregulation of the channel via p38α, ultimately resulting in aberrant hyperexcitability.…”
Section: Alternative Strategies For Modulation Of Nav Channelsmentioning
confidence: 99%
“…Curiously, however, in the absence of a functional Pro-Gly-Try 1945 motif, it is observed that p38 phosphorylation of Nav 1.6 enhances peak current density [ 122 ], indicating that p38 phosphorylation of Nav1.6 may have opposing effects on Nav1.6-mediated neuronal excitability dependent on the function of Nedd4-2. Haploinsufficiency of Nedd4-2 is linked to increased seizure susceptibility [ 151 ], which is a hallmark symptom of prodromal AD [ 30 , 66 , 67 ]. Thus, it is possible that dysfunctional Nedd4-2 reduces Nav1.6 internalization and allows functional upregulation of the channel via p38α, ultimately resulting in aberrant hyperexcitability.…”
Section: Alternative Strategies For Modulation Of Nav Channelsmentioning
confidence: 99%